Comparative Study of Master Oil (MO) and Lophira Lanceolata (Ochnaceae) Oil (LLO) Lubricants in Sewing Machines - Jamu Benson Yerima; G. O Mokoro; D. William; S. D Najoji (International Journal of Applied Sciences and Smart Technologies, 2022)
In this paper, the Flash point, Fire point, Cloud point, Pour point, and Volatility of master oil (MO) and locally processed lophira lanceolata oil (LLO) were determined using standard laboratory methods. The results show that LLO has lower volatility which means it can stay longer in moving parts of a machine than MO. Also, the results show that the flash point and fire point of the lubricants lie within the maximum operating temperature range (300 oC) of sewing machines. The high pour point (14 oC) and cloud point (23 oC) of LLO limit its use as a lubricant in low temperate regions of the world as opposed to -14 oC and -7 oC respectively for MO which has universal application.  This implies LLO needs to be chemically blended with some additive agents that can lower its Pour point so that it can favourably compete with other lubricants used in sewing machines worldwide.